Esthetic Rehabilitation with Ceramic Laminate Veneers and a Zirconia Crown with Ceramic Veneering on a Metal Substrate: A Clinical Case Report - Sobrinho, Leonardo Henrique David dos Santos (Brazilian Journal of Case Reports, 2021)
Smile esthetics is one of the main demands in contemporary dentistry. Minimally invasive rehabilitations with ceramic laminate veneers have been widely used to correct esthetic and functional disharmonies. However, cases involving darkened substrates or teeth with a metal post require differentiated restorative strategies. This case report presents an esthetic rehabilitation using ceramic laminate veneers combined with a zirconia crown with ceramic veneering on tooth 11 with a cast metal post. The protocol included digital planning, intraoral scanning, virtual diagnostic waxing, esthetic mock-up, minimally invasive preparations, and adhesive cementation. The final outcome demonstrated esthetic integration, functionality, and high patient satisfaction. This work highlights the importance of appropriate material selection and digital technologies to optimize clinical outcomes in complex cases.